1985
DOI: 10.1111/j.1365-2362.1985.tb00288.x
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of renin release during experimental myocardial ischaemia

Abstract: An increase in plasma renin activity (PRA) following experimental coronary occlusion has previously been demonstrated in anaesthetized and conscious dogs. The purpose of the present study was to analyse the mechanism of this renin release. In two distinct models of myocardial ischaemia in anaesthetized dogs--i.e. occlusion of the left-anterior descending coronary artery (model A, n = 21) and atrial pacing in the presence of stenosis of the left-anterior descending coronary artery (model B, n = 23), an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Studies have shown [20,21] that the renin-angiotensin system is activated in patients with ischemic heart disease and that endogenous angiotensin II participates in the control of coronary blood flow in the presence of an activated reninangiotensin system [18,42,43]. Enalaprilat is an antagonist of angiotensin II in isolated coronary arteries [44] and antagonizes the coronary vasoconstrictor effect of angiotensin II [45].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown [20,21] that the renin-angiotensin system is activated in patients with ischemic heart disease and that endogenous angiotensin II participates in the control of coronary blood flow in the presence of an activated reninangiotensin system [18,42,43]. Enalaprilat is an antagonist of angiotensin II in isolated coronary arteries [44] and antagonizes the coronary vasoconstrictor effect of angiotensin II [45].…”
Section: Discussionmentioning
confidence: 99%